2023
DOI: 10.2478/ama-2023-0039
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Seismic Damage Analysis for Concrete Gravity Dams: A Case Study of Oued Fodda Dam

Abstract: One of the major dangers for seismic damage of concrete dams is the propagation of cracks in dam concrete. The present study undertakes a numerical investigation of the seismic damage for Oued Fodda concrete gravity dam, located in the northwest of Algeria, considering the impacts of properties of joints along the dam-foundation rock interface and cross-stream earthquake excitation. Three-dimensional transient analyses for coupled dam-foundation rock system are carried out using Ansys software. The hydrodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In seismic high-intensity areas, severe concrete dam accidents not only result in significant damage to the surrounding facilities but also pose a substantial threat to the life and property of downstream residents [ 8 , 9 ]. Therefore, it is necessary to study the dynamic response patterns and failure mode patterns of concrete gravity dams subjected to strong earthquakes to evaluate their seismic safety [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In seismic high-intensity areas, severe concrete dam accidents not only result in significant damage to the surrounding facilities but also pose a substantial threat to the life and property of downstream residents [ 8 , 9 ]. Therefore, it is necessary to study the dynamic response patterns and failure mode patterns of concrete gravity dams subjected to strong earthquakes to evaluate their seismic safety [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study by [10] analyzed seismic damage for concrete gravity dams using a numerical examination of the seismic damage for the Oued Fodda concrete gravity dam, which is situated in northwest Algeria. The findings of the study was suggested that, the frictional joints model can more effectively lessen the seismic response and damage hazard of the dam body.…”
Section: Introductionmentioning
confidence: 99%